Steganography in IEEE 802.11 OFDM symbols1. Issue 2 (29th March 2011) - Szczypiorski, Krzysztof; Mazurczyk, Wojciech
Abstract: This paper presents a new steganographic method called wireless padding (WiPad). It is based on the insertion of hidden data into the padding of frames at the physical layer of wireless local area networks (WLANs). A performance analysis based on a Markov model, previously introduced and validated by the authors, is provided for the method in relation to the IEEE 802.11 a/g standards. Its results prove that maximum steganographic bandwidth for WiPad is as high as 1.1 Mbit/s for data frames and 0.44 Mbit/s for acknowledgment frames. To the authors' best knowledge this is the most capacious of all the known steganographic network channels. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : This paper presents a new steganographic method called wireless padding (WiPad). It is based on the insertion of hidden data into the padding of frames at the physical layer of wireless local area networks (WLANs). A performance analysis based on a Markov model, previously introduced and validated by the authors, is provided for the method in relation to the IEEE 802.11 a/g standards.